(untitled) (Annals of Medical Research, 2021)
Aim: An estimation of accurate oxygen saturation is a critical in the management of patients with heart failure (HF). However, obtaining peripheral arterial blood samples may be technically difficult in some cases. The purpose of this study was to evaluate the correlation of pulse oximetry SO2 with arterial SO2 in patients with HF reduced ejection fraction (HFrEF). Material and Methods: In total, 29 consecutive patients who were admitted to cardiology clinics with HFrEF were prospectively enrolled in this study. We enrolled all patients if the chief physician ordered an atrial blood gas analysis. Simultaneous atrial blood gas sample and pulse oximetry measurements were collected and compared. The strength of association between atrial blood gas and pulse oximetry measurements was determined by Pearson correlation and Bland and Altman analysis.Results: We evaluated 29 heart failure patients (the mean age was; 70.7±10.9, 44.8 % of patients were male) with a mean EF of 29.6 ± 5.5. We observed that the mean pulse oximetry SO2 and arterial SO2 in the study were 92.8 ± 4.4 and 93 ± 5.2, respectively. We found significantly positive linear correlation between two methods according to Pearson analysis (r = 0.683, p 0.001). A low bias was found between two methods according to Bland and Altman method (-0.2296, p = 0.23).Conclusion: The present data may suggest that pulse oximetry oxygen saturation is an acceptable substitute for the arterial oxygen saturation in patients with HFrEF.